CHRISTOLOGY AS RECONSTRUCTED ADAMO LOGY - Jesudasan, Ignatius (Asian Horizons, 2008)
The thesis of this article is that the Gospels were constructed in midrashical!>’ parallel continuity and contrast to the biblical history of Israel. In order to prove the thesis the author follows certain hypothetical assumptions. the first of which is that the biblical canonically recorded history of Israel is clearly divisible into seven stages.corresponding to the week-long pattern of God’s creation and rest according to the Priest!ycode found in Gen 1:3 - 2:4. The opinion of the author is that the Adamic myth. which had ended the history of Israel on a more pessimistic note. needed its happy-ending corrective from the Christological gospels of the reconciling and reconciled God and Father of the lord JesusChrist as also the Father of all who believed in Jesus as the son of God. lcsudasan argues that theological metaphors were intended ethical!y to transform socio-political and economic history.